Electrode, all-solid-state battery, and method for manufacturing electrode
The electrode design with fluoride-coated composite particles and imidazoline dispersants addresses the issue of sulfide electrolyte deterioration in all-solid-state batteries, enhancing durability by reducing resistance and maintaining conductivity.
Patent Information
- Application Number
- JP2022119622
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-07-27
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2042-07-27
AI Technical Summary
Sulfide solid electrolytes in all-solid-state batteries experience accelerated deterioration due to direct contact with active materials, leading to increased resistance over time, which impairs ionic conductivity.
The electrode design includes composite particles coated with a fluoride solid electrolyte layer between the active material and a sulfide solid electrolyte layer, utilizing an imidazoline compound as a dispersant to maintain ion and electron conduction paths, thereby reducing volume fluctuations and resistance increase.
The proposed electrode structure effectively reduces the rate of resistance increase during durability tests, maintaining efficient ion and electron conductivity by dispersing composite particles and minimizing reaction resistance.
Smart Images

Figure 0007609828000005 
Figure 0007609828000006 
Figure 0007609828000007
Abstract
Description
[Technical field]
[0001] The present disclosure relates to an electrode, an all-solid-state battery, and a method for manufacturing the electrode. [Background technology]
[0002] JP 2014-154407 A (Patent Document 1) discloses a composite active material including composite particles containing an oxide solid electrolyte that coats an active material, and a sulfide solid electrolyte that coats the composite particles. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2014-154407 A Summary of the Invention [Problem to be solved by the invention]
[0004] Hereinafter, solid electrolyte may be abbreviated as "SE." For example, sulfide solid electrolyte may be abbreviated as "sulfide SE."
[0005] Sulfide SE has both high ionic conductivity and excellent moldability. Sulfide SE is suitable for bulk-type all-solid-state batteries. However, direct contact of sulfide SE with active materials in electrodes can accelerate degradation of sulfide SE. Degradation of sulfide SE can result in, for example, loss of ionic conductivity.
[0006] In order to reduce direct contact between the sulfide SE and the active material, it has been proposed to form composite particles by coating the active material with an oxide SE. In addition, it has also been proposed to coat the composite particles with a sulfide SE to promote the formation of an interface between the composite particles and the sulfide SE. The combination of the active material, oxide SE, and sulfide SE is expected to reduce the initial resistance. However, there is room for improvement in the rate of increase in resistance after durability testing.
[0007] An object of the present disclosure is to reduce the rate of increase in resistance after durability testing. [Means for solving the problem]
[0008] The technical configuration and effects of the present disclosure will be described below. However, the mechanism of action in this specification includes assumptions. The mechanism of action does not limit the technical scope of the present disclosure.
[0009] 1. The electrode includes an active material layer. The active material layer includes a composite particle and an imidazoline-based compound. The composite particle includes a core particle and a coating layer. The coating layer covers at least a portion of the surface of the core particle. The core particle includes an active material. The coating layer includes a first layer and a second layer. At least a portion of the first layer is disposed between the core particle and the second layer. The first layer includes a first solid electrolyte. The second layer includes a second solid electrolyte. The first solid electrolyte is a fluoride. The second solid electrolyte is a sulfide.
[0010] The active material expands and contracts due to charging and discharging. In the active material layer, ion conductive paths and electron conductive paths are formed around the active material. For example, an ion conductive material such as sulfide SE can form the ion conductive path, and an electron conductive material such as carbon black can form the electron conductive path. The ion conductive path and the electron conductive path can follow the volumetric change of the active material to some extent.
[0011] When the active material aggregates in the active material layer, large volume fluctuations occur locally, and it is believed that the ionic and electronic conductive paths cannot keep up with the large volume fluctuations, accelerating an increase in resistance.
[0012] The active material layer of the present disclosure includes composite particles and an imidazoline-based compound. In the process of forming the active material layer, the imidazoline-based compound can act as a dispersant for the constituent materials of the active material layer. According to the new findings of the present disclosure, the imidazoline-based compound can impart good dispersibility to sulfide SE in particular.
[0013] The composite particles are covered with a coating layer. The coating layer contains sulfide SE. Thus, the imidazoline-based compound can impart good dispersibility to the composite particles. It is believed that the dispersion of the composite particles (active material) can disperse volume fluctuations. Therefore, it is believed that the ion conduction path and the electron conduction path are easily maintained, and the rate of increase in resistance is reduced.
[0014] Furthermore, the composite particles of the present disclosure also contain a fluoride SE. In conventional composite particles, an oxide SE (e.g., LiNbO 3 According to the new findings of the present disclosure, the fluoride SE is less likely to increase reaction resistance during endurance testing than the oxide SE. In the composite particles, the presence of the fluoride SE (first layer) between the active material (core particle) and the sulfide SE (second layer) is expected to further reduce the rate of increase in resistance.
[0015] 2. In the electrode according to the above item "1", the imidazoline compound may be represented by, for example, the following formula (1):
[0016] [ka]
[0017] In the above formula (1), R 1 R is an alkyl group or a hydroxyalkyl group having 1 to 22 carbon atoms. 2 is an alkyl or alkenyl group having 10 to 22 carbon atoms.
[0018] 3. In the electrode according to the above item "1" or "2", the imidazoline compound may be 0.05 to 0.1 parts by mass per 100 parts by mass of the composite particles.
[0019] 4. In the electrode according to any one of the above items "1" to "3", the first solid electrolyte may be represented by, for example, the following formula (2): Li 6-nx M x F 6 …(2) In the above formula (2), x satisfies 0 < x < 2. M is at least one selected from the group consisting of a half-metal atom and a metal atom other than Li. n indicates the oxidation number of M.
[0020] 5. In the above formula (2), M may contain an atom having an oxidation number of +4.
[0021] 6. In the above formula (2), M may contain an atom having an oxidation number of +3.
[0022] 7. In the above formula (2), M may contain at least one selected from the group consisting of Ca, Mg, Al, Y, Ti, and Zr.
[0023] 8. The all-solid-state battery includes the electrode according to any one of the above "1" to "7".
[0024] The all-solid-state battery is expected to have a low resistance increase rate during durability.
[0025] 9. The method for manufacturing the electrode includes the following (a) and (b). (a) Prepare a slurry containing composite particles, an imidazoline-based compound, and a dispersion medium. (b) Form an active material layer by applying the slurry. The composite particles include core particles and a coating layer. The coating layer covers at least a part of the surface of the core particles. The core particles contain an active material. The coating layer includes a first layer and a second layer. At least a part of the first layer is disposed between the core particles and the second layer. The first layer contains a first solid electrolyte. The second layer contains a second solid electrolyte. The first solid electrolyte is a fluoride. The second solid electrolyte is a sulfide.
[0026] The imidazoline-based compound can impart good dispersibility to the composite particles in the slurry. Since it is difficult for the composite particles to form aggregates, an active material layer with a good dispersion state of the composite particles can be formed.
[0027] 10. The above (a) may include, for example, the following (a1) and (a2): (a1) A first slurry containing an imidazoline compound and a dispersion medium is prepared. (a2) preparing a second slurry by dispersing composite particles in the first slurry;
[0028] It is expected that the dispersibility of the composite particles will be further improved by adding the composite particles to the slurry after the imidazoline-based compound.
[0029] Hereinafter, an embodiment of the present disclosure (hereinafter may be abbreviated as "the present embodiment") and an example of the present disclosure (hereinafter may be abbreviated as "the present embodiment") will be described. However, the present embodiment and the present embodiment do not limit the technical scope of the present disclosure. The present embodiment and the present embodiment are illustrative in all respects. The present embodiment and the present embodiment are non-restrictive. The technical scope of the present disclosure encompasses all modifications within the meaning and scope equivalent to the description of the claims. For example, it is originally intended that any configuration may be extracted from the present embodiment and the present embodiment, and that they may be arbitrarily combined. [Brief description of the drawings]
[0030] [Figure 1] FIG. 1 is a conceptual diagram showing an example of a composite particle in this embodiment. [Diagram 2] FIG. 2 is a schematic flow chart of the method for producing an electrode in this embodiment. [Diagram 3] FIG. 3 is a conceptual diagram of the all-solid-state battery in this embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0031] <Terms and definitions> The words "comprise," "include," "have," and variations thereof (e.g., "consisting of") are open-ended. The open-ended form may or may not include additional elements in addition to the required elements. The words "consisting of" are closed-ended. However, the closed form does not exclude additional elements that are normally associated with the technology or that are unrelated to the technology disclosed. The words "consisting essentially of..." are semi-closed. The semi-closed form allows for the addition of elements that do not substantially affect the basic and novel characteristics of the technology disclosed.
[0032] "At least one of A and B" includes "A or B" as well as "A and B." "At least one of A and B" can also be written as "A and / or B."
[0033] Expressions such as "may" and "may" are used in the permissive sense, meaning "to have the possibility," rather than in the obligatory sense, meaning "to have to."
[0034] Unless otherwise specified, the order of execution of the steps, operations, and the like included in various methods is not limited to the order described. For example, the steps may proceed simultaneously. For example, the steps may be performed in sequence.
[0035] Elements expressed in the singular form include the plural form unless otherwise specified. For example, a "particle" can mean not only "one particle" but also "an aggregate of particles (powder, powder, particle group)."
[0036] For example, a numerical range such as "m to n%" includes an upper limit and a lower limit. That is, "m to n%" indicates a numerical range of "m% or more and n% or less." Furthermore, "m% or more and n% or less" includes "more than m% and less than n%." Furthermore, a numerical value arbitrarily selected from within the numerical range may be set as a new upper limit or lower limit. For example, a new numerical range may be set by arbitrarily combining a numerical value within the numerical range with a numerical value described in another part of this specification, in a table, in a figure, or the like.
[0037] All numerical values are modified by the term "about." The term "about" may mean, for example, ±5%, ±3%, ±1%, etc. All numerical values may be approximations that may vary depending on the application of the disclosed technology. All numerical values may be expressed with significant figures. Measurements may be average values of multiple measurements. The number of measurements may be three or more, five or more, or ten or more. In general, the more measurements are taken, the more reliable the average value is expected to be. Measurements may be rounded off based on the number of significant figures. Measurements may include errors associated with, for example, the detection limits of the measuring device.
[0038] If the compound has a stoichiometric formula (e.g., LiCoO 2 When a stoichiometric formula is expressed by a formula such as "LiCoO ", the stoichiometric formula is merely a representative example of the compound. The compound may have a non-stoichiometric composition. For example, lithium cobalt oxide may be expressed by a formula such as "LiCoO 2 ", unless otherwise specified, the lithium cobalt oxide is not limited to the composition ratio of "Li / Co / O=1 / 1 / 2" and may contain Li, Co, and O in any composition ratio. Furthermore, doping or substitution with trace elements may also be permitted.
[0039] "Semi-metals" include B, Si, Ge, As, Sb, and Te. "Metals" refers to elements from Groups 1 to 16 of the periodic table, other than "H, B, Si, Ge, As, Sb, Te, C, N, P, O, S, and Se." When an inorganic compound contains at least one of a semi-metal and a metal and F, the semi-metal and the metal may have a positive (+) oxidation number.
[0040] The term "electrode" is a general term for positive and negative electrodes. The electrode may be a positive electrode or a negative electrode.
[0041] The "thickness" of the coating layer, the first layer, and the second layer can be measured by the following procedure. A sample is prepared by embedding the composite particles in a resin material. The sample is subjected to a cross-section processing by an ion milling device. For example, a product named "Arblade (registered trademark) 5000" (or an equivalent product) manufactured by Hitachi High-Technologies Corporation may be used. The cross-section of the sample is observed by a SEM (Scanning Electron Microscope). For example, a product named "SU8030" (or an equivalent product) manufactured by Hitachi High-Technologies Corporation may be used. For each of the 10 composite particles, the thickness of the target portion (coating layer, first layer, second layer) is measured in 20 fields of view. The arithmetic average of the thicknesses of the 200 points in total is regarded as the thickness of the target portion.
[0042] The thickness of each layer may be measured in an element mapping image by SEM-EDX (Energy Dispersive X-ray Spectrometry). In the element mapping image, an element representative of each part is selected. As an example, Ni may be selected as the representative element of the core particle (active material), F as the representative element of the first layer (fluoride SE), and S as the representative element of the second layer (sulfide SE).
[0043] The "coverage" is measured by the following procedure. A cross-sectional sample of the composite particle is prepared in the same manner as the sample for measuring the thickness of the coating layer. In the cross-sectional SEM image, the length (L 0 ) is measured. The length (L 1 ) is measured. L 1 L 0 The percentage of the value divided by is the coverage. The coverage is measured for each of 20 composite particles. The arithmetic average of the 20 coverages is considered to be the "coverage."
[0044] For example, by applying image processing to the element mapping image obtained by SEM-EDX, L 0 and L 1 may be calculated.
[0045] A "hollow particle" refers to a particle in which the area of the cavity in the center is 30% or more of the cross-sectional area of the entire particle in a cross-sectional image of the particle (e.g., a cross-sectional SEM image, etc.). A "solid particle" refers to a particle in which the area of the cavity in the center is less than 30% of the cross-sectional area of the entire particle in a cross-sectional image of the particle.
[0046] "D50" refers to the particle size at which the cumulative frequency of the smaller particle sizes reaches 50% in a volume-based particle size distribution. D50 can be measured using a laser diffraction particle size distribution analyzer.
[0047] The "average Feret diameter" is measured in a two-dimensional image of a particle (e.g., a SEM image, etc.). The arithmetic mean of the maximum Feret diameters of 20 or more particles is the "average Feret diameter".
[0048] The "solid content" refers to the ratio of the total mass of the components other than the dispersion medium to the total mass of the slurry. The solid content is expressed as a percentage.
[0049] <Electrode> The electrode includes an active material layer. The electrode may further include, for example, a substrate, etc. For example, the active material layer may be disposed on the surface of the substrate. The substrate may be, for example, sheet-shaped. The substrate may have, for example, electronic conductivity. The substrate may function, for example, as a current collector. The substrate may include, for example, a metal foil, etc. The metal foil may include, for example, at least one selected from the group consisting of Al, Cu, Ni, Fe, and Ti. The metal foil may be, for example, an Al foil, an Al alloy foil, a Ni foil, a Cu foil, a Cu alloy foil, or a stainless steel foil. When the electrode is a positive electrode, the substrate may include, for example, an Al foil, etc. When the electrode is a negative electrode, the substrate may include, for example, a Ni foil, a Cu foil, etc. The substrate may have a thickness of, for example, 5 to 50 μm.
[0050] The active material layer may have a thickness of, for example, 1 to 1000 μm, or 10 to 500 μm. The active material layer includes composite particles and an imidazoline-based compound. The active material layer may further include an auxiliary material. The auxiliary material may include, for example, at least one selected from the group consisting of an ion conductive material, an electron conductive material, and a binder. The active material layer may be composed of, for example, 1 to 50% of the auxiliary material, 0.01 to 0.3% of the imidazoline-based compound, and the remainder of the composite particles, in mass fraction.
[0051] <Imidazoline compounds> The active material layer includes an imidazoline-based compound. The imidazoline-based compound can act as a dispersant. The imidazoline-based compound can impart good dispersibility, particularly to sulfides SE. The presence of the imidazoline-based compound can cause the composite particles to have a good dispersion state. The composite particles (active material) having a good dispersion state can reduce the rate of increase in resistance during durability.
[0052] The imidazoline compound has an imidazoline skeleton. The imidazoline skeleton includes a nitrogen-containing heterocyclic structure. The imidazoline skeleton can be derived from imidazole. The imidazoline compound may be represented by, for example, the following formula (1).
[0053] [ka]
[0054] In the above formula (1), R 1 R may be, for example, an alkyl group or a hydroxyalkyl group. 1 may have, for example, a carbon number of 1 to 22. In the hydroxyalkyl group, for example, a hydroxyl group may be bonded to the terminal carbon atom opposite to the carbon atom bonded to N (nitrogen atom).
[0055] In the above formula (1), R 2R may be, for example, an alkyl or alkenyl group. 2 may have, for example, a carbon number of 10 to 22. In the alkenyl group, the position and number of double bonds are optional.
[0056] The imidazoline compound may include, for example, 1-hydroxyethyl-2-alkenylimidazoline, etc. The active material layer may include one type of imidazoline compound alone, or may include two or more types of imidazoline compounds.
[0057] The amount of the imidazoline compound is arbitrary. For example, the amount of the imidazoline compound may be 0.01 to 0.3 parts by mass, 0.01 to 0.2 parts by mass, or 0.05 to 0.1 parts by mass, relative to 100 parts by mass of the composite particles. When the amount of the imidazoline compound is 0.05 parts by mass or more, for example, a reduction in the resistance increase rate is expected. When the amount of the imidazoline compound is 0.1 parts by mass or less, for example, a reduction in the initial resistance is expected.
[0058] 《Composite particles》 The active material layer includes composite particles. The composite particles include an active material, a fluoride SE, and a sulfide SE. The sulfide SE forms a part of the coating layer. The imidazoline-based compound acts on the coating layer, which can impart good dispersibility to the composite particles. It is expected that the good dispersion state of the composite particles in the active material layer will reduce the rate of increase in resistance during durability.
[0059] FIG. 1 is a conceptual diagram showing an example of a composite particle in this embodiment. The composite particle 30 includes a core particle 10 and a coating layer 20. The D50 of the composite particle 30 may be, for example, 1 to 30 μm, 2 to 20 μm, 3 to 15 μm, 3 to 6 μm, or 4 to 5 μm. The composite particle 30 may have any shape. The composite particle 30 may be, for example, spherical, ellipsoidal, flaky, fibrous, or the like.
[0060] The composite particles 30 may be formed by any method. For example, the composite particles may be formed by a mechanochemical method. For example, a two-stage coating process may be performed by a particle composite device. That is, the core particles 10, the fluoride SE, and the sulfide SE are sequentially charged and mixed in the particle composite device to form the coating layer 20. An example of the particle composite device is "Nobilta NOB-MINI" manufactured by Hosokawa Micron Corporation. However, any mixing device, granulating device, etc. may be used as long as the particles can be composited.
[0061] 《Coating layer》 The coating layer 20 covers at least a part of the surface of the core particle 10. For example, the coating layer 20 may be formed so as to fill in the unevenness of the surface of the core particle 10. The coating layer 20 may cover the entire surface of the core particle 10. The coating layer 20 may cover a part of the surface of the core particle 10. The coating layer 20 may be distributed in an island shape on the surface of the core particle 10. The coverage may be, for example, 50 to 100%, 60 to 100%, 70 to 100%, 80 to 100%, or 90 to 100%. The higher the coverage, the more reduced the initial resistance is expected, for example.
[0062] The thickness of the covering layer 20 may be, for example, 6 to 300 nm, or 11 to 150 nm. As the covering layer 20 is thinner, for example, a reduction in initial resistance is expected.
[0063] The coating layer 20 includes a first layer 21 and a second layer 22. At least a portion of the first layer 21 is disposed between the core particle 10 and the second layer 22. For example, the first layer 21 may directly coat the surface of the core particle 10. For example, the second layer 22 may coat the entire first layer 21. The second layer 22 may coat a portion of the first layer 21. There may be a portion of the first layer 21 exposed from the second layer 22. There may be a portion of the second layer 22 in direct contact with the core particle 10.
[0064] (1st layer, Fluoride SE) The first layer 21 is, so to speak, the "lower layer". The first layer 21 may, for example, cover the entire core particle 10 without any gaps. The first layer 21 may have a thickness of, for example, 1 to 100 nm or 1 to 50 nm. The thinner the first layer 21 is, for example, the reduction of the initial resistance is expected.
[0065] The first layer 21 contains a first solid electrolyte (first SE). The first SE is a fluoride. The fluoride SE tends to have a low tendency for the reaction resistance to increase during durability.
[0066] The first SE can have any composition as long as it contains F. The first SE may contain, for example, Li and F. The first SE may be represented by, for example, the following formula (2). Li 6-nx M x F 6 …(2) In the above formula (2), x satisfies 0 < x < 2. M is at least one selected from the group consisting of a semi-metal atom and a metal atom excluding Li. n indicates the oxidation number of M.
[0067] M may consist of a single atom or may consist of a plurality of types of atoms. When M consists of a plurality of types of atoms, n indicates the weighted average of the oxidation numbers of each atom. For example, when M contains Ti (oxidation number = +4) and Al (oxidation number = +3), the molar ratio of Ti to Al is "Ti / Al = 3 / 7", and x = 1, n becomes 3.3 according to the formula "n = 0.3×4 + 0.7×3".
[0068] x may satisfy, for example, 0.1 ≦ x ≦ 1.9, 0.2 ≦ x ≦ 1.8, 0.3 ≦ x ≦ 1.7, 0.4 ≦ x ≦ 1.6, 0.5 ≦ x ≦ 1.5, 0.6 ≦ x ≦ 1.4, 0.7 ≦ x ≦ 1.3, 0.8 ≦ x ≦ 1.2, or 0.9 ≦ x ≦ 1.1.
[0069] M may contain, for example, an atom having an oxidation number of +4. M may contain, for example, an atom having an oxidation number of +3. M may contain, for example, an atom having an oxidation number of +4 and an atom having an oxidation number of +3.
[0070] M may, for example, include at least one selected from the group consisting of Ca, Mg, Al, Y, Ti, and Zr. M may, for example, include at least one selected from the group consisting of Al, Y, and Ti. M may, for example, include at least one selected from the group consisting of Al and Ti.
[0071] The first SE may be expressed, for example, by the following formula (3). Li 3-x Ti x Al 1-x F 6 …(3) In the above formula (3), x may satisfy, for example, 0≦x≦1, 0.1≦x≦0.9, 0.2≦x≦0.8, 0.3≦x≦0.7, or 0.4≦x≦0.6.
[0072] The first SE may be, for example, particulate. That is, the first layer 21 may be, for example, a particulate layer. The particulate layer is an aggregate of particles. The average Feret's diameter of the first SE may be, for example, 0.1 to 1 times the thickness of the first layer 21.
[0073] (2nd layer, sulfide SE) The second layer 22 is, so to speak, an "upper layer." The second layer 22 may form the outermost layer of the composite particle 30. The second layer 22 may surround the core particle 10 without any gaps. The second layer 22 may be thicker than the first layer 21, for example. The second layer 22 may have a thickness of, for example, 5 to 200 nm, or 10 to 100 nm.
[0074] The second layer 22 includes a second solid electrolyte (second SE). The second SE is a sulfide. The sulfide SE can exhibit high ionic conductivity. The second SE can have any composition as long as it contains S (sulfur). The second SE may contain, for example, Li, P, and S. The second SE may further contain, for example, O, Ge, Si, etc. The second SE may further contain, for example, halogens, etc. The second SE may further contain, for example, I, Br, etc. The second SE may be, for example, a glass ceramic type or an argyrodite type. The second SE may be, for example, LiI-LiBr-Li 3 P.S. 4 , Li 2 S-SiS 2 , LiI-Li 2 S-SiS 2 , LiI-Li 2 SP 2 S 5 , LiI-Li 2 O-Li 2 SP 2 S 5 , LiI-Li 2 SP 2 O 5 , LiI-Li 3 PO 4 -P 2 S 5 , Li 2 S-GeS 2 -P 2 S 5 , Li 2 SP 2 S 5 , Li 4 P 2 S 6 , Li 7 P 3 S 11 , and Li 3 P.S. 4 may contain at least one selected from the group consisting of:
[0075] For example, "LiI-LiBr-Li 3 P.S. 4 " is LiI, LiBr and Li 3 P.S. 4The second SE may be produced by mixing Li and Li in any molar ratio. For example, the second SE may be produced by a mechanochemical method. 2 SP 2 S 5 " is Li 3 P.S. 4 Contains: 3 P.S. 4 For example, Li 2 S and P 2 S 5 And "Li 2 S / P 2 S 5 =75 / 25 (molar ratio)". The molar ratio may be specified by adding a number before LiI, etc. For example, "10LiI-15LiBr-75Li 3 P.S. 4 " is "LiI / LiBr / Li 3 P.S. 4 This indicates that the two are mixed in a molar ratio of 10 / 15 / 75.
[0076] The second SE may be, for example, particulate. That is, the second layer 22 may be, for example, a particle layer. The particle layer is an aggregate of particles. The average Feret diameter of the second SE may be equal to or less than the thickness of the second layer 22. The average Feret diameter of the second SE may be equal to or less than 1 / 3 (one third) of the maximum Feret diameter of the core particle 10. When the size of the second SE is sufficiently small compared to the size of the core particle 10, the coating layer 20 tends to easily fill in the unevenness of the surface of the core particle 10. This is expected to improve, for example, the coverage rate. The average Feret diameter of the second SE may be, for example, 5 to 200 nm, or 10 to 100 nm.
[0077] Core Particle The core particle 10 is a base material of the composite particle 30. The composite particle 30 may contain one core particle 10 alone. The composite particle 30 may contain a plurality of core particles 10. The core particle 10 may be, for example, a secondary particle. The secondary particle is an aggregate of primary particles. The D50 of the secondary particle may be, for example, 1 to 30 μm, 2 to 20 μm, 3 to 15 μm, 3 to 6 μm, or 4 to 5 μm. The average Feret's diameter of the primary particles may be, for example, 0.01 to 3 μm.
[0078] The core particle 10 may have any shape. The core particle 10 may be, for example, spherical, ellipsoidal, flake-like, fibrous, etc. The core particle 10 may be a solid particle or a hollow particle.
[0079] The core particle 10 includes an active material. The active material can cause an electrode reaction. The core particle 10 may include, for example, a positive electrode active material. That is, the electrode may be a positive electrode. The positive electrode active material may include any component. The positive electrode active material is, for example, LiCoO 2 , LiNiO 2 , LiMnO 2 , LiMn 2 O 4 , Li(NiCoMn)O 2 , Li(NiCoAl)O 2 , Li(NiCoMnAl)O 2 , and LiFePO 4 For example, "Li(NiCoMn)O 2 "(NiCoMn)" in "Li(NiCoMn)O" indicates that the sum of the composition ratios in the parentheses is 1. As long as the sum is 1, the amount of each component is arbitrary. 2 For example, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 , LiNi 0.4 Co 0.3 Mn 0.3 O 2 , LiNi 0.5 Co 0.2 Mn 0.3 O2 , LiNi 0.5 Co 0.3 Mn 0.2 O 2 , LiNi 0.5 Co 0.4 Mn 0.1 O 2 , LiNi 0.5 Co 0.1 Mn 0.4 O 2 , LiNi 0.6 Co 0.2 Mn 0.2 O 2、 LiNi 0.6 Co 0.3 Mn 0.1 O 2、 LiNi 0.6 Co 0.1 Mn 0.3 O 2、 LiNi 0.7 Co 0.1 Mn 0.2 O 2、 LiNi 0.7 Co 0.2 Mn 0.1 O 2、 LiNi 0.8 Co 0.1 Mn 0.1 O 2、 and LiNi 0.9 Co 0.05 Mn 0.05 O 2 Li(NiCoAl)O 2 For example, LiNi 0.8 Co 0.15 Al 0.05 O 2 etc. may be included.
[0080] The positive electrode active material may be represented, for example, by the following formula (4). Li 1-y Ni x M 1-x O 2 …(4) 0.5≦x≦1 -0.5≦y≦0.5 In the above formula (4), M may contain, for example, at least one selected from the group consisting of Co, Mn, and Al. x may be, for example, 0.6 or more, 0.7 or more, 0.8 or more, or 0.9 or more.
[0081] The positive electrode active material may contain, for example, an additive. The additive may be, for example, a substitutional solid solution atom or an interstitial solid solution atom. The additive may be an adherent adhering to the surface of the positive electrode active material (primary particle). The adherent may be, for example, a simple substance, an oxide, a carbide, a nitride, a halide, or the like. The addition amount may be, for example, 0.01 to 0.1, 0.02 to 0.08, or 0.04 to 0.06. The addition amount indicates the ratio of the amount of the additive to the amount of the positive electrode active material. The additive may contain, for example, at least one selected from the group consisting of B, C, N, halogen, Sc, Ti, V, Cu, Zn, Ga, Ge, Se, Sr, Y, Zr, Nb, Mo, In, Sn, W, and lanthanoids.
[0082] The core particle 10 may contain, for example, a negative electrode active material. That is, the electrode may be a negative electrode. The negative electrode active material may contain any component. The negative electrode active material may be, for example, natural graphite, artificial graphite, soft carbon, hard carbon, Si, SiO x (0 < x < 2), Si-based alloy, Sn, SnO x (0 < x < 2), Li, Li-based alloy, and Li 4 Ti 5 O 12 and may contain at least one selected from the group consisting of. SiO x (0 < x < 2) may be doped with, for example, Mg or the like. A composite material may be formed by supporting an alloy-based active material (such as Si) on a carbon-based active material (such as graphite).
[0083] 《Ion Conductive Material》 The active material layer may contain, for example, an ion conductive material. The ion conductive material may form an ion conductive path in the active material layer. The ion conductive material may be particulate. The ion conductive material may have a D50 of, for example, 0.01 to 1 μm, 0.01 to 0.95 μm, or 0.1 to 0.9 μm. The amount of the ion conductive material is arbitrary. The amount of the ion conductive material may be, for example, 1 to 200 parts by volume, 50 to 150 parts by volume, or 50 to 100 parts by volume, relative to 100 parts by volume of the composite particles. The ion conductive material may contain, for example, a sulfide SE, a fluoride SE, or the like. The sulfide SE and fluoride SE contained in the ion conductive material may be the same type as or different from the sulfide SE and fluoride SE contained in the composite particles.
[0084] 《Electronic Conductive Material》 The active material layer may contain, for example, an electronic conductive material. The electronic conductive material may form an electronic conductive path in the active material layer. The amount of the electronic conductive material is arbitrary. The amount of the electronic conductive material may be, for example, 0.1 to 10 parts by mass with respect to 100 parts by mass of the composite particles. The electronic conductive material may contain any component. The electronic conductive material may contain, for example, at least one selected from the group consisting of carbon black (CB), vapor grown carbon fiber (VGCF), carbon nanotube (CNT) and graphene flake (GF). The CB may contain, for example, at least one selected from the group consisting of acetylene black (AB), Ketjen Black (registered trademark), and furnace black.
[0085] Binder The binder can bind solids together. The amount of the binder is arbitrary. The amount of the binder may be, for example, 0.1 to 10 parts by mass with respect to 100 parts by mass of the composite particles. The binder can contain any component. The binder may contain, for example, at least one selected from the group consisting of rubber-based binders and fluorine-based binders.
[0086] The rubber-based binder may include, for example, at least one selected from the group consisting of butadiene rubber (BR), hydrogenated butadiene rubber, styrene butadiene rubber (SBR), hydrogenated styrene butadiene rubber, nitrile butadiene rubber (NBR), hydrogenated nitrile butadiene rubber, and ethylene propylene rubber (EPM).
[0087] The fluorine-based binder may include at least one selected from the group consisting of polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), and polytetrafluoroethylene (PTFE). The binder may include a polymer blend, polymer alloy, copolymer, etc. of each of the materials exemplified here.
[0088] A binder containing an SBR-derived component is also referred to as an "SBR-based binder." The SBR-based binder may contain, by mass fraction, for example, 10% or more of an SBR-derived component, 30% or more of an SBR-derived component, 50% or more of an SBR-derived component, 70% or more of an SBR-derived component, or 90% or more of an SBR-derived component. The SBR-based binder may be made of SBR.
[0089] The binder may contain a thermoplastic resin. For example, the active material layer containing the thermoplastic resin may be liquefied and then resolidified by hot pressing. As a result, the active material layer is expected to become dense. The active material layer is expected to become dense, which improves the battery characteristics (e.g., input / output characteristics, etc.). The thermoplastic resin may contain, for example, SBR. SBR may have a softening point suitable for hot pressing.
[0090] The affinity between various materials can be evaluated by the distance (Ra) in the Hansen space. The "Hansen space" is a three-dimensional space represented by the Hansen solubility parameter (HSP). In the Hansen space, the smaller the distance (Ra) between two materials, the higher the affinity between the two materials. For example, the distance (Ra) between a sulfide SE and an imidazoline compound is 1 ) is the distance between the sulfide SE and the binder (Ra 2 ) may be smaller than "Ra 1 / Ra 2 <1" may be satisfied. 1 / Ra 2 <1" is expected to improve the dispersion effect. It is believed that the imidazoline-based compound can preferentially adsorb to sulfide SE compared to the binder, thereby enhancing the dispersion effect. For example, 2 -Ra 1 ≧0.5MPa 0.5 The rubber-based binder may satisfy the relationship of "distance (Ra 2 ) tends to be large. In other words, rubber-based binders tend to have a lower affinity for sulfide SE than fluorine-based binders. When the active material layer contains a rubber-based binder, it is thought that the dispersion effect of the imidazoline-based compound is easily obtained.
[0091] Below is an example of calculating distance in a Hansen space. The distance between the sulfide SE and the imidazoline compound (Ra 1 )=10.7MPa 0.5 Distance between sulfide SE and rubber binder (Ra 2 )=11.6MPa 0.5 Distance between sulfide SE and fluorine-based binder (Ra 2 )=3.8MPa 0.5
[0092] <Electrode manufacturing method> FIG. 2 is a schematic flow chart of the method for producing an electrode in this embodiment. The method for producing an electrode in this embodiment (hereinafter may be abbreviated as "this production method") includes "(a) preparation of a slurry" and "(b) formation of an active material layer". This production method may further include, for example, "(c) pressing" or the like.
[0093] (a) Preparation of slurry The present manufacturing method includes preparing a slurry containing composite particles, an imidazoline-based compound, and a dispersion medium. The slurry may further include an auxiliary material (such as a binder). For example, the composite particles, the imidazoline-based compound, and the auxiliary material may be dispersed in the dispersion medium to form a slurry. In the present manufacturing method, any mixing device, kneading device, dispersion device, etc. may be used. For example, an ultrasonic homogenizer, etc. may be used.
[0094] Each material may be added at once or sequentially. When the materials are added sequentially, a dispersion process may be performed after each addition. When the materials are added sequentially, the imidazoline compound may be added prior to the addition of the composite particles. That is, the present manufacturing method may include "(a1) Preparation of a first slurry" and "(a2) Preparation of a second slurry". The first slurry is prepared to contain an imidazoline compound and a dispersion medium. The second slurry is prepared by dispersing the composite particles in the first slurry. By adding the composite particles after dispersing the imidazoline compound, it is expected that the dispersion effect will be improved. The auxiliary material may be mixed into the first slurry or into the second slurry.
[0095] The solid content of the slurry can be adjusted as desired depending on, for example, the coating method, etc. The solid content of the slurry may be, for example, 50 to 70%.
[0096] In the slurry, the details of the components other than the dispersion medium are as described above. The dispersion medium may contain any component. For example, the dispersion medium may contain at least one selected from the group consisting of aromatic hydrocarbons, esters, alcohols, ketones, and lactams. For example, the dispersion medium may contain at least one selected from the group consisting of tetralin, butyl butyrate, heptane, and N-methyl-2-pyrrolidone (NMP).
[0097] Butyl butyrate is expected to be less likely to degrade sulfide SE than, for example, NMP, etc. Tetralin is expected to be less likely to degrade sulfide SE than, for example, butyl butyrate and NMP, etc. When the dispersion medium contains tetralin, for example, it is expected that the initial resistance will be reduced.
[0098] (b) Formation of active material layer The present manufacturing method includes forming an active material layer by applying a slurry. For example, the active material layer can be formed by applying the slurry to the surface of the substrate and drying it. The details of the substrate are as described above. In the present manufacturing method, any coating device can be used. For example, a die coater, a roll coater, or the like can be used. In the present manufacturing method, any drying device can be used. For example, a hot air drying device, a hot plate, an infrared drying device, or the like can be used.
[0099] (c)Press The present manufacturing method may include, for example, subjecting the active material layer to a press process. For example, cold press processing may be performed, or hot press processing may be performed. In the present manufacturing method, any press device may be used. For example, a roll press device or the like may be used. When hot press processing is performed, the press temperature may be adjusted depending on, for example, the type of binder. The press temperature may be, for example, 80 to 180°C.
[0100] The electrode can be manufactured as described above. The electrode can be cut to a predetermined size according to the specifications of the all-solid-state battery.
[0101] <All-solid-state battery> FIG. 3 is a conceptual diagram of the all-solid-state battery in this embodiment. The all-solid-state battery 200 includes a power generating element 150. The all-solid-state battery 200 may include, for example, an exterior body (not shown). The exterior body may house the power generating element 150. The exterior body may have any shape. The exterior body may be, for example, a pouch made of a metal foil laminate film, or a case made of metal.
[0102] The all-solid-state battery 200 may include a single power generating element 150, or may include a plurality of power generating elements 150. The plurality of power generating elements 150 may form, for example, a series circuit or a parallel circuit.
[0103] The power generating element 150 includes a positive electrode 110, a separator layer 130, and a negative electrode 120. That is, the all-solid-state battery 200 includes electrodes. At least one of the positive electrode 110 and the negative electrode 120 includes composite particles and an imidazoline-based compound.
[0104] The separator layer 130 may have a thickness of, for example, 1 to 100 μm. The separator layer 130 is interposed between the positive electrode 110 and the negative electrode 120. The separator layer 130 separates the positive electrode 110 from the negative electrode 120. The separator layer 130 has ion conductivity and does not have electronic conductivity. The separator layer 130 includes an ion conductive material. The separator layer 130 may include, for example, a sulfide SE or the like. The separator layer 130 may further include, for example, a fluoride SE and a binder or the like. The details of each material are as described above. The sulfide SE may be the same or different between the separator layer 130 and the positive electrode 110. The sulfide SE may be the same or different between the separator layer 130 and the negative electrode 120.
[0105] The all-solid-state battery 200 may include a restraining member (not shown). The restraining member applies pressure to the power generating element 150 from outside the exterior body. The pressure applied to the power generating element 150 is also referred to as "restraining pressure". The restraining pressure may be, for example, 0.1 to 50 MPa, or 1 to 20 MPa. The restraining member has any structure. The restraining member may include, for example, two end plates, a bolt, a nut, and the like. The two end plates may hold the power generating element 150 in between. The bolt may connect the two end plates. The nut may fasten the bolt. EXAMPLES
[0106] <Sample preparation> Electrodes according to Nos. 1 to 4 and all-solid-state batteries were manufactured as follows. Hereinafter, for example, "electrode according to No. 1" will also be simply referred to as "No. 1".
[0107] No.1 (Preparation of negative electrode slurry) The following materials were prepared: Active material: Li 4 Ti 5 O 12 Paint additive: BYK-Chemie "DISPERBYK (registered trademark)-109" Ion conductor: 10LiI-15LiBr-75Li 3 P.S. 4 (D50=0.9μm) Electronic Conductive Material: VGCF Binder: SBR binder Dispersion medium: Tetralin
[0108] The paint additive included an imidazoline compound (1-hydroxyethyl-2-alkenylimidazoline).
[0109] A slurry was prepared by mixing active material, paint additives, ion conductive material, electronic conductive material, binder, and dispersion medium using an ultrasonic homogenizer (UH-50 manufactured by SMT). The solid content ratio was "active material / paint additives / ion conductive material / electronic conductive material / binder = 100 / 1.88 / 33.6 / 1.1 / 0.86 (mass ratio)". The solid content of the slurry was 56%.
[0110] (Preparation of Positive Electrode Slurry) The following materials were prepared: Composite particle: Core particle (LiNi 0.8 Co 0.15 Al 0.05 O 2 ) / 1st layer (Li 2.7 Ti 0.3 Al 0.7 F 6 ) / 2nd layer (Li 3 P.S. 4 ) Paint additive: BYK-Chemie "DISPERBYK (registered trademark)-109" Ion conductor: 10LiI-15LiBr-75Li 3 P.S. 4 (D50=0.9μm) Electronic Conductive Material: VGCF, AB Binder: SBR binder Dispersion medium: Tetralin
[0111] A slurry was prepared by mixing the composite particles, paint additives, ion conductive material, electronic conductive material, binder, and dispersion medium using an ultrasonic homogenizer. The solid content ratio was "composite particles / paint additives / ion conductive material / VGCF / AB / binder = 100 / 0.05 / 32.0 / 3.06 / 0.3 / 0.42 (mass ratio)". The solid content of the slurry was 65.5%.
[0112] The specific mixing procedure was as follows: The binder, electronic conductive material (AB), and dispersion medium were added to the container. The mixture was dispersed using an ultrasonic homogenizer. Next, composite particles were added to the container, and dispersion was performed again. Next, a paint additive (imidazoline-based compound) was added to the container, and dispersion was performed again. Finally, an ion conductive material (sulfide SE) and an electronic conductive material (VGCF) were added, and dispersion was performed again.
[0113] That is, in the manufacturing process of the slurry No. 1, the composite particles were added before the imidazoline-based compound. In Table 1 below, the order of adding the materials in No. 1 is written as "composite particles → imidazoline-based compound."
[0114] (Preparation of Separator Slurry) The following materials were prepared: Ion conductor: LiI-LiBr-Li 2 SP 2 S 5 (Glass ceramic type, D50=2.5μm) Binder solution: Solute: SBR binder (mass fraction 5%), Solvent: Heptane Dispersion medium: heptane
[0115] In a polypropylene container, the ion conductive material, the binder solution, and the dispersion medium were mixed for 30 seconds by an ultrasonic homogenizer. After mixing, the container was set on a shaker. The container was shaken by the shaker for 3 minutes to prepare a slurry.
[0116] (Preparation of power generating element) The slurry for the positive electrode was applied to the surface of a substrate (Al foil, 15 μm thick) using a blade applicator. After application, the slurry was dried for 30 minutes on a hot plate (set temperature 100° C.) to form an active material layer. That is, a positive electrode including an active material layer and a substrate was formed.
[0117] The negative electrode slurry was applied to the surface of a substrate (Ni foil, thickness 22 μm) using a blade applicator. After application, the slurry was dried for 30 minutes on a hot plate (set temperature 100° C.) to form an active material layer. That is, a negative electrode including an active material layer and a substrate was formed. The weight of the negative electrode was adjusted so that the ratio of the specific charge capacity of the negative electrode to the specific charge capacity of the positive electrode was 1.0. The specific charge capacity of the positive electrode was 200 mAh / g.
[0118] The positive electrode was pressed. After pressing, the separator slurry was applied to the surface of the positive electrode using a die coater. After application, the slurry was dried for 30 minutes on a hot plate (set temperature 100°C) to form a separator layer. This completed the preparation of the first unit. The first unit was pressed using a roll press device. The linear pressure was 2 ton / cm.
[0119] The negative electrode was pressed. After pressing, the separator slurry was applied to the surface of the negative electrode using a die coater. After application, the slurry was dried for 30 minutes on a hot plate (set temperature 100°C) to form a separator layer. This completed the preparation of the second unit. The second unit was pressed using a roll press device. The linear pressure was 2 ton / cm.
[0120] The separator slurry was applied to the surface of a temporary support (metal foil). After application, the slurry was dried on a hot plate (set temperature 100° C.) for 30 minutes to form a separator layer.
[0121] The separator layer on the temporary support was transferred to the surface of the first unit. The planar shapes of the first unit and the second unit were adjusted by punching. The first unit and the second unit were laminated so that the separator layer of the first unit faced the separator layer of the second unit. This formed the power generation element. The power generation element was hot pressed using a roll press device. The pressing temperature was 160°C. The linear pressure was 2 ton / cm.
[0122] (Production of all-solid-state batteries) An exterior body (a pouch made of Al laminated film) was prepared. A power generating element was enclosed in the exterior body. A restraining member was prepared. The restraining member was attached to the outside of the exterior body so that a restraining pressure of 5 MPa was generated. Through the above steps, an all-solid-state battery was manufactured.
[0123] No.2 In "Preparation of Positive Electrode Slurry", the positive electrode slurry was prepared by the following mixing procedure. The binder, AB, and dispersion medium were placed in a container. The mixture was dispersed using an ultrasonic homogenizer. Next, the ion conductive material and VGCF were placed in the container, and the dispersion process was carried out again. Next, the paint additive was placed in the container, and the dispersion process was carried out again. Finally, the composite particles were placed in the container, and the dispersion process was carried out again.
[0124] That is, in the manufacturing process of the slurry of No. 2, the composite particles were added after the imidazoline compound. In the following Table 1, the order of adding materials in No. 2 is written as "imidazoline compound → composite particles." Except for this, the electrode and the all-solid-state battery were manufactured in the same way as No. 1.
[0125] No.3 An electrode and an all-solid-state battery were manufactured in the same manner as in No. 2, except that in the "preparation of slurry for positive electrode", the amount of the paint additive was changed to 0.1 parts by mass per 100 parts by mass of the composite particles.
[0126] No.4 An electrode and an all-solid-state battery were manufactured in the same manner as in No. 1, except that in the "preparation of slurry for positive electrode", no paint additive was used.
[0127] <Evaluation> The SOC (State Of Charge) of the solid-state battery was adjusted to 50%. The solid-state battery was discharged for 2 seconds at a time rate of 60.2 C in a thermostatic chamber (set temperature 25°C). The initial resistance was calculated from the voltage drop and current during discharge.
[0128] Note that "C" is the symbol for the current rate. At a rate of 1C, the rated capacity of the battery is discharged in 1 hour.
[0129] After the initial resistance was measured, a durability test was carried out, that is, a pulse charge-discharge cycle was carried out under the following conditions:
[0130] Test temperature: 80℃ SOC range: 50~60% Charge / discharge cycle count: 800
[0131] After the durability test, the post-durability resistance was measured in the same manner as the initial resistance. The resistance increase rate was calculated by dividing the post-durability resistance by the initial resistance.
[0132] [Table 1]
[0133] As shown in Table 1 above, Nos. 1 to 3 had a lower resistance increase rate than No. 4. The active material layers of Nos. 1 to 3 contain an imidazoline-based compound. The active material layer of No. 4 does not contain an imidazoline-based compound.
[0134] The resistance increase rate of No. 2 was lower than that of No. 1. In the manufacturing process of the slurry of No. 2, the imidazoline compound was added before the composite particles.
[0135] The resistance increase rate of No. 3 was lower than that of No. 2. No. 3 contained a larger amount of imidazoline-based compound than No. 2. [Explanation of symbols]
[0136] 10 core particle, 20 coating layer, 21 first layer, 22 second layer, 30 composite particle, 110 positive electrode, 120 negative electrode, 130 separator layer, 150 power generating element, 200 all-solid-state battery.
Claims
1. An active material layer is included, the active material layer includes composite particles, an imidazoline-based compound, and an ion conductive material; The imidazoline compound is present in an amount of 0.05 to 0.1 parts by mass relative to 100 parts by mass of the composite particles; The composite particle includes a core particle and a coating layer, the coating layer covers at least a part of the surface of the core particle, The core particle includes an active material, The coating layer includes a first layer and a second layer, At least a portion of the first layer is disposed between the core particle and the second layer, the first layer includes a first solid electrolyte; the second layer includes a second solid electrolyte; the first solid electrolyte is a fluoride; The second solid electrolyte is a sulfide, the ion conductive material includes a third solid electrolyte; The third solid electrolyte is a sulfide. electrode.
2. The imidazoline compound has the formula (1): 【Chemistry 1】 is represented by In the formula (1), R 1 is an alkyl or hydroxyalkyl group having 1 to 22 carbon atoms; R 2 is an alkyl or alkenyl group having 10 to 22 carbon atoms; 2. The electrode of claim 1.
3. The second layer is thicker than the first layer, 2. The electrode of claim 1.
4. The first solid electrolyte has the formula (2): <h2 style=";text-align:left;direction:ltr">Li<h2 style=";text-align:left;direction:ltr"> 6-nx <h2 style=";text-align:left;direction:ltr"> 8<h2 style=";text-align:left;direction:ltr"> x <h2 style=";text-align:left;direction:ltr"> F<h2 style=";text-align:left;direction:ltr"> 6 <h2 style=";text-align:left;direction:ltr"> …(2) is represented by In the formula (2), x satisfies 0<x<2, M is at least one selected from the group consisting of metalloid atoms and metal atoms other than Li; n indicates the oxidation number of M; 4. The electrode according to claim 1 .
5. In the formula (2), M contains an atom having an oxidation number of +4; 5. The electrode of claim 4.
6. In the formula (2), M contains an atom having an oxidation number of +3; 5. The electrode of claim 4.
7. In the formula (2), M includes at least one selected from the group consisting of Ca, Mg, Al, Y, Ti, and Zr; 5. The electrode of claim 4.
8. The second layer extends along a surface of the core particle, The coverage of the second layer is 50 to 100%; The coverage is calculated by dividing L 1 by L 0 , L 0 represents the length of the outline of the core particle in the cross section of the composite particle, The L 1 represents the length of the portion of the contour of the core particle that is covered with the second solid electrolyte.
2. The electrode of claim 1.
9. The active material layer further contains a rubber-based binder.
2. The electrode of claim 1.
10. The third solid electrolyte has a different composition from the second solid electrolyte.
2. The electrode of claim 1.
11. The average Feret diameter of the second solid electrolyte is smaller than D50 of the third solid electrolyte, 2. The electrode of claim 1.
12. The average Feret diameter of the second solid electrolyte is 5 nm or more and 100 nm or less, The D50 of the third solid electrolyte is greater than 100 nm and less than or equal to 1 μm.
12. The electrode of claim 11.
13. 2. A method comprising the steps of: All-solid-state battery.
14. (a) preparing a slurry containing composite particles, an imidazoline-based compound, an ion conductive material, and a dispersion medium; and (b) forming an active material layer by applying the slurry; Including, The (a) is (a1) preparing a first slurry containing the imidazoline-based compound and the dispersion medium; (a2) preparing a second slurry by dispersing the composite particles in the first slurry; and (a3) preparing a third slurry by dispersing the ionically conductive material in the second slurry. Including, The imidazoline compound is present in an amount of 0.05 to 0.1 parts by mass relative to 100 parts by mass of the composite particles; The composite particle includes a core particle and a coating layer, the coating layer covers at least a part of the surface of the core particle, The core particle includes an active material, The coating layer includes a first layer and a second layer, At least a portion of the first layer is disposed between the core particle and the second layer, the first layer includes a first solid electrolyte; the second layer includes a second solid electrolyte; the first solid electrolyte is a fluoride; The second solid electrolyte is a sulfide, the ion conductive material includes a third solid electrolyte; The third solid electrolyte is a sulfide. A method for manufacturing an electrode.
Citation Information
Patent Citations
Composite active material and manufacturing method thereof
JP2014154407A
All-solid-state lithium secondary battery and manufacturing method thereof
JP2020161364A
Positive electrode for all-solid-state battery
JP2021193647A
Anode material for lithium ion battery and lithium ion battery including the same
US20160118652A1
Positive electrode material, and battery
WO2021187391A1